Pathways to violent extremism: a qualitative comparative analysis of the US far-right. Issue 1 (2nd January 2019) - Fahey, Susan; Simi, Pete
ABSTRACT: In this research, we analyzed extensive life history interviews and open-source data on a sample of 35 current and former white supremacists. These individuals had all committed ideologically motivated violence, some of which clearly exhibited a greater degree of planning, who we termed the "planned violence" sample while those in the "spontaneous violence" sample had committed more opportunistic violence, such as "wilding-style" attacks on available victims. Using Qualitative Comparative Analysis (QCA), we examined whether there were important differences in the presence and combination of prior risk factors, such as offending history, truancy, delinquent peers, family members involved in extremism, a lower- or working-class childhood and academic failure, which led to the outcome condition of either planned or spontaneous violence. Our findings demonstrated differences between the two samples, with the spontaneous violence sample demonstrating higher risk than the planned violence sample. However, no support was garnered for the identification of distinct pathways of homogeneous risk factors among either sample of violent offenders.